Edukasi Gizi Seimbang Lansia dan Pemeriksaan Kesehatan pada Lansia Komunitas Olahraga Woodball: Balanced Nutrition Education and Health Checkup for the Elderly Woodball Community - Wilda Yunieswati; Ika Yulianingsih; Muhammad Ishaq Gery (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Elderly is a group susceptible to non-communicable diseases due to a decrease in the function of the body's organs and a decrease in the body's immune system. Education related to balanced nutrition and health & nutritional status checks of the elderly are carried out to reduce the risk of non-communicable diseases such as obesity and hypertension in the elderly. The targets involved are elderly people from the Pamulang WoodBall Club (PWbC) Community, South Tangerang City. Education related to balanced nutrition for elderly is provided by lecture and discussion methods using leaflet. Meanwhile, a health & nutritional status checks was carried out by measuring weight, height and blood pressure. The percentage increase in target knowledge related to balanced nutrition is 41.4%, so it can be concluded that there was an increase in knowledge of balanced nutrition in the elderly. Most of the elderly were overweight (30.4%) and obese (30.4%) and had pre-hypertension (43.5%) and hypertension (26.1%).